Pengaruh pertumbuhan UMKM, inflasi, dan tingkat pengangguran terhadap pertumbuhan ekonomi di Indonesia - Junaidi; Asnah Tul Ramadani; Zulfa Eliza (Jurnal Investasi Islam, 2020)
This study aims to determine the effect of MSMEs (Micro, Small and Medium Enterprises), inflation, and unemployment on economic growth in Indonesia. In this study only 14 years were taken. This research uses quantitative research methods. The technique used in this study is Purposive Sampling, which is a deliberate sampling technique. The type of data used in this study is secondary. Data analysis techniques used in this study are the analysis of classic assumptions, multiple linear regression, and hypotheses. The formulation if the problem of the influence of MSME growth on economic growth in Indonesia, the effect of inflation on economic growth in Indonesia, the effect of unemployment on economic growth in Indonesia, the influence of MSME, inflation and, unemployment rates on economic growth in Indonesia. Partial results (T test) the influence of MSME (X1) of 0.010 <0.05, inflation (X2) of 0.029 <0.05, unemployment (X3) of 0.013 <0.05 and a significant positive effect on economic growth in Indonesia. F test results (Simultaneous) showed a significant value of 0.007 <0.05 meaning that MSME, inflation, and unemployment simultaneously had a significant effect on economic growth in Indonesia. Then from the R-square test results of 0.656 or 65.6%. The magnitude of these results can be explained by the MSME variables,